Gambaran Aktivitas Fisik Remaja dalam Upaya Pencegahan Masalah Gizi di Panti Asuhan Ainul Yaqin Jambi - Hatussaadah, Siti Fati; Aisah, Aisah; Fatmawati, Tina Yuli (3031-8572, 2024)
Adolescents are defined as young people aged 10-19 years. Adolescents experience rapid growth and development, and are included in a group that is vulnerable to nutritional problems, so they need to get the attention of many parties. This increasing lack of physical activity is a health problem that needs attention and can be addressed immediately. Lack of physical activity has also been identified as a risk factor for chronic disease. As an effort to prevent nutritional problems, this research was carried out to find out factors related to nutritional problems, one of which was adolescent physical activity among MTS students as many as 14 respondents at the Ainul Yaqin Orphanage, Jambi City. The results of the research showed that all respondents fell into the category of early adolescence, 100% of the respondents were male (50%) and 7 respondents were female (50%). Based on the level of physical activity of teenagers, the average number of respondents had a light physical activity level of 9 respondents (64.3%) and 5 respondents had a moderate level of physical activity (35.7%), there were no respondents with a heavy physical activity level. The conclusion in this study was that the majority of respondents, namely 9 respondents, had low levels of physical activity (64.3%). It is recommended that partners continue to motivate teenagers to increase their daily physical activity, so that their health status can be optimal. Future researchers can carry out further research with different variables and methods in efforts to prevent nutritional problems. The targeted output is scientific publication in accredited national journals.